Optimization of 2-Acylaminocycloalkylthiophene Derivatives for Activity against Staphylococcus aureus RnpA - Michaelle Chojnacki; Xufeng Cao; Daniel P. Flaherty; Paul M. Dunman (MDPI AG, 2021)
Staphylococcus aureus is well-recognized to cause debilitating bacterial infections that are difficult to treat due to the emergence of antibiotic resistance. As such, there is a need to develop new antimicrobials for the therapeutic intervention of S. aureus disease. To that end, S. aureus RnpA is an essential enzyme that is hypothesized to participate in two required cellular processes, precursor tRNA (ptRNA) maturation and mRNA degradation. Corresponding high throughput screening campaigns have identified the phenylcarbamoyl cyclic thiopenes as a chemical class of RnpA inhibitors that display promising antibacterial effects by reducing RnpA ptRNA and mRNA degradation activities and low human cell toxicity. Herein, we perform a structure activity relationship study of the chemical scaffold. Results revealed that the cycloalkane ring size and trifluoroacetamide moiety are required for antibacterial activity, whereas modifications of the para and/or meta positions of the pharmacophore's phenyl group allowed tuning of the scaffold's antimicrobial performance and RnpA inhibitory activity. The top performing compounds with respect to antimicrobial activity also did not exhibit cytotoxicity to human cell lines at concentrations up to 100 µM, greater than 100-fold the minimum inhibitory concentration (MIC). Focused studies of one analog, RNP0012, which exhibited the most potent antimicrobial and inhibition of cellular RnpA activities revealed that the compound reduced bacterial burden in a murine model of S. aureus disease. Taken together, the results presented are expected to provide an early framework for optimization of next-generation of RnpA inhibitor analogues that may represent progenitors of a new class of antimicrobials.